Atrial fibrillation and breast cancer—Vicious twins? A systematic review and meta-analysis - Yao, Xiongda; Hu, Qingwen; Liu, Xiao; Ling, Qing; Leng, Yurong; Zhao, Huilei; Yu, Peng; Ma, Jianyong; Zhao, Yujie; Liu, Menglu; Yang, Renqiang (Frontiers in Cardiovascular Medicine, 2023)
Background Epidemiological studies suggest a bidirectional association between atrial fibrillation and breast cancer. This study aimed to conduct a meta-analysis to elucidate the prevalence of atrial fibrillation among breast cancer patients, and the bidirectional association between atrial fibrillation and breast cancer. Methods PubMed, the Cochrane Library, and Embase were searched to identify studies reporting the prevalence, incidence, and bidirectional association between atrial fibrillation and breast cancer. The study was registered with PROSPERO (CRD42022313251). Levels of evidence and recommendations were assessed by the Grading of Recommendations Assessment, Development and Evaluation (GRADE). Results Twenty-three studies (17 retrospective cohort studies, 5 case-control studies and 1 cross-sectional study) involving 8,537,551 participants were included. Among patients with breast cancer, the prevalence of atrial fibrillation was 3% (11 studies; 95% CI: 0.6 to 7.1%) and the incidence was 2.7% (6 studies; 95% CI: 1.1 to 4.9%). Breast cancer was associated with increased risk of atrial fibrillation (5 studies; hazard ratio [HR]: 1.43, 95% CI: 1.12 to 1.82, I2 = 98%). Atrial fibrillation was also significantly associated elevated risk of breast cancer (5 studies HR: 1.18, 95% CI: 1.14 to 1.22, I2 = 0%). Grade assessment shown low certainty of the evidence for the risk of atrial fibrillation and moderate certainty of the evidence for the risk of breast cancer. Conclusion Atrial fibrillation is not uncommon in patients with breast cancer and vice versa. There is a bidirectional association between atrial fibrillation (low certainty) and breast cancer (moderate certainty).